Public Sector Reforms and New Public Management: Exploratory Evidence from Australian Public Sector - Chowdhury, Anup; Shil, Nikhil Chandra (Asian Development Policy Review, 2017)
This study is about the exploration of public sector reform agendas in the context of New Public Management initiatives in Australia. Australian public sector has been adopted as the field for investigation. The purpose of this study is to understand how new public management ideals become embedded in the new financially and managerially oriented Australian public sector which may be a learning for public sector in Southeast Asia. Evidence supported that the Australian Public Sector has operated within the context of a range of reformed government policies, strategies and laws. The primary catalyst of reforms in Australia was generated by government regulatory policies. It is also evident that the Australian Public Sector had made changes in their structure and operation to achieve cost-efficiency, budget accountability and an improved customer focus in service delivery. The research also demonstrates that implementation of reforms initiatives are the functions of New Public Management in the key areas of financial management. These findings are consistent with the view that changes to the Australian public sector promoted managerial accountability and a culture of performance.